Development of Basic Finger Shapes Indonesian Traditional Dance Application Using Color-Based Hand Gesture Recognition - Henokh Kristiawan; Wahyu Teja Kusuma; Risqy Siwi Pradini (Journal of Enhanced Studies in Informatics and Computer Applications, 2024)
UNESCO stated that Indonesian traditional dance is a world cultural heritage that must be preserved and maintained. Efforts made by the government to preserve traditional dance are still not successful. Research shows that students have difficulty in learning traditional Indonesian dance exercises. Therefore, this study develops a solution that focuses on the difficulty of learning the basic finger postures in traditional Indonesian dances. This is important because fingers are instruments in dancing that have meaningful forms, such as Closed Urang Chopsticks, Nyempurit, Ngruji, Open Urang Chopsticks, Ke-pelan, Baya Mangap, and Ngithing. Learning the practice of basic finger postures aims to provide an independent learning experience through repetitive movements to strengthen or strengthen. This research has succeeded in making a real-time Color-Based Hand Gesture Recognition application for reliable Android devices. This is evidenced by applications that can function well in test scenarios with varying lighting and background conditions. Finally, students can learn the hand gestures of traditional Indonesian dances independently with ease. In addition, the application of the results of this research also contributes to becoming a learning medium in the current era of Blended Learning. Suggestions for future research are to increase the accuracy of Nyempurit and Ngithing attitudes.